NCAA in-season coaching time regulations negate strength and conditioning gains in women`s division-II basketball team - Papadakis, Z.; Stamatis, A.; Padgett, R. N.; Sanders, B. K. (International Journal of Sports Science, 2019)
Strength and conditioning (SC) coaches are responsible for student-athletes` conditioning. National Collegiate Athletic Association (NCAA) time regulations may hinder SC coach`s success. This study aimed to characterize the effects of NCAA in-season time restrictions of SC training on preseason lower-body power performance in a collegiate DII women`s basketball team. During pre-season 14 players completed 3 hrs/wk of SC, while the in-season time was reduced to 2 hrs/wk. Average countermovement jump (CMJ) height and peak average power (PAP) were measured 1/wk for 10 weeks. CMJ and PAP examined relatively, allometrically scaled and analyzed using repeated measures ANOVAs primary for time and secondary for position. Statistical significance was set at p 2=.263) and scaled PAP scores (F(4.8, 62.4) = 2.78, p=.0265, ?2=.176). Pre-season PAP was higher than in-season controlling for player position (Est = 93.22 W, SE = 38.88, p = .033). Forwards had higher PAP than guards (Est = 400.6 W, SE=157.7, p =.022). Scaled PAP was higher pre-season than in-season controlling for player position (Est = 5.727(W · kg-0.67), SE = .85, p =.002). SC program success is subjected to the NCAA regulations. Three hrs/wk seem to be the threshold that below that pre-season lower-body performance gains during the in-season are diminished. NCAA regulations may need to be revised so they do not influence the work of SC coaches.